2011
DOI: 10.1159/000320790
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer of Zeste Homologue 2 Expression in Breast Carcinoma Smears in Relationship with p53, Ki-67 and Other Prognostic Parameters

Abstract: Background: The polycomb group protein enhancer of zeste homologue 2 (EZH 2) has been reported as a marker of aggressive breast cancer. The aim of this study was to investigate the correlation between the expression of EZH 2 with p53 and Ki-67 expression and other clinicopathological parameters in primary breast carcinomas in order to determine the role of the above marker as a prognosticator of tumor aggressiveness and patient outcome. Patients and Methods: One hundred primary operable breast cancer patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
2
4
0
2
Order By: Relevance
“…We also found a significant correlation between high EZH2 expression and both p53 overexpression and high Ki-67 proliferative index. This is consistent with previous experimental findings that suggest roles for p53 and Ki-67 in regulating EZH2 via its promoter [ 21 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…We also found a significant correlation between high EZH2 expression and both p53 overexpression and high Ki-67 proliferative index. This is consistent with previous experimental findings that suggest roles for p53 and Ki-67 in regulating EZH2 via its promoter [ 21 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…Nineteen studies provided sufficient data for the meta-analysis of the correlation between EZH2 expression and clinicopathological characteristics ( Table 4 ) [ 14 17 , 19 , 21 , 23 , 24 , 26 , 31 , 32 , 34 – 37 , 41 44 ]. Esophageal carcinoma, renal cell carcinoma, breast cancer gastric cancer, and NSCLC were investigated in detail.…”
Section: Resultsmentioning
confidence: 99%
“…In a subgroup of triple-negative patients, EZH2-positive staining was detected in 85.7% of patients (33). When all breast cancer subtypes were combined, the EZH2 expression rate was 47.4-64.0% (16,17). The corresponding mean mRNA levels of EZH2 in luminal A, luminal B, HER2 + , basal-like and normal-like subtypes were -0.476, 0.145, 0.186, 0.778 and -0.853, respectively (34).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, aberrant expression of EZH2 was identified in a variety of solid tumors and might be correlated with the aggressive features of breast cancer such as higher histological grade, increased tumor cell proliferation, lymph node invasion and larger tumor size (4,(9)(10)(11)(12)(13)(14)(15). Although the aggressive effects of EZH2 have been confirmed (4,16,17), the prognostic value of EZH2 in breast cancer remains unclear (9,(16)(17)(18). Kleer et al found that high levels of EZH2 mRNA were correlated with poor distant metastasis-free survival (DMFS) and that overexpression of EZH2 protein predicted inferior overall survival (OS) and disease-free survival (DFS) (9).…”
Section: Introductionmentioning
confidence: 99%